Synthesis and evaluation of novel chromanone and quinolinone analogues of uniflorol as anti-leishmanial agents. Issue 3 (March 2020) - Castro, Helena; Cruz, Tânia; de Aguiar Amaral, Patrícia; da Silva Cardoso, Paula; Alsaffar, Ahmed; Farrell, Patrick; Tomás, Ana M.; Barlow, James W.
Abstract: Within this work, we describe the design and synthesis of a range of novel chromanones and quinolinones, based on natural products reported to possess anti-leishmanial action. The core heterocycles were obtained either via classical or ionic liquid mediated Kabbe condensation in the case of chromanones, or aqueous Sonogashira based alkynylation followed by acid-catalysed cyclisation in the case of quinolinones. Upon testing in promastigotes, axenic amastigotes and Leishmania -infected macrophages, compound 13c was identified as displaying interesting activity, inhibiting axenic amastigotes and intracellular amastigotes with IC50 s of 25.3 and 24.6μM respectively. Abstract : Natural product chemistry, Organic chemistry; Pharmaceutical chemistry; Chromanone, Quinolinone, Leishmania